Adaptation of liquid rocket engine shell manufacturing technology to modern capabilities of CAD-CAM systems and 5-axis coordinate CNC machines - Voichyshen O. (НТУ «ДП», 2024)
In my study I have described and substantiated: 1. The planing process using a special cutting tool on a 5-coordinate CNC machine for machining spiral surfaces of liquid engines shells has been proposed for the first time. 2. The principles of programming 5-axis CNC machines [1] for planing using modern CAM-systems [2] have been developed for the first time.
Keywords: CAD-CAM; 5-axis coordinate CNC